Answer:
The fourth term is 11 and the tenth term is 29
Explanation:
Let us use the given formula to solve the question
∵ A(n) = 2 + (n - 1)(3) is the formula of the nth term of an sequence
∵ n is the position of the term in the sequence
∴ For the fourth term n = 4
∴ For the tenth term n = 10
→ Substitute n by 4 in the formula above to find the fourth term
∵ A(4) = 2 + (4 - 1)(3)
∴ A(4) = 2 + (3)(3)
∴ A(4) = 2 + 9
∴ A(4) = 11
∴ The fourth term is 11
→ For the tenth term put n = 10
∵ n = 10
∵ A(10) = 2 + (10 - 1)(3)
∴ A(10) = 2 + (9)(3)
∴ A(10) = 2 + 27
∴ A(10) = 29
∴ The tenth term is 29